Diagnosis and Treatment of Antisocial Personality Disorder: A Case Report - Patricia Wulandari (Scientia Psychiatrica, 2020)
Introduction: Antisocial personality disorder (ASPD) defines patterns of behavior that are irresponsible for social, exploitative, and unproblematic issues that begin in early childhood or adolescence and are manifested by changes in the life phase. This case report aimed to describe antisocial personality disorder experienced by a girl in Aceh, Indonesia. Case presentation. A woman, 19 years old, a college student, living in a suburban area, came to consult to hospital with complaints of anxiety and difficulty sleeping. The patient claimed that she often wanted to hurt and persecute others. She often tries to hurt other people but does not get caught because she said the act was carried out accidentally. When she was a child, she liked to torture animals and she did it without guilt and pity. Lately patient felt the desire to hurt others is getting bigger. Conclusion: The management of antisocial personality disorder can be adjusted to the circumstances and background or risk factors of the disorder, and treatment is used to reduce symptoms.